The term "ama/aman" to designate plants: the cultural heritage of Amazonia and the West Indies. - (:unkn) unknown (My University, 2023)
There are linguistic and cultural similarities between Creole and certain populations in southern Benin, notably those Gungbe and Fongbe speakers. Both territories are former colonies of France, characterised by multilingualism and multiculturalism. What's more, there is a strong similarity in endogenous healthcare practices involving the use of medicinal plants. Some plant designations are also identical, such as the term "ama/aman".
Keywords: African Research